Keynes’s Time in the Times of Capitalism - Belluzzo, Luiz Gonzaga (Brazilian Keynesian Review, 2015)
This paper aims to discuss the process of construction of the thought of John Maynard Keynes about capitalism. Therefore, it discusses the economic, social and political transformations undergone in the world, in general, and in England, in particular, that have shaped the reality about which he reflected. It also discusses the evolution of these reflections until his magnum opus, The General Theory of Employment, Interest and Money, in which he presents the limits and possibilities of a monetary economy of production.